Pengaruh Jenis Rhizobakteria terhadap Pertumbuhan dan Hasil Tanaman Kedelai (Glycine max (L). Merril) - ARDYAWAN, I GEDE; RAKA, I GUSTI NGURAH; ARTHA, I NENGAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.1, Januari 2018, 2018)
The Influence of Type of Rhizobacteria on Growth and Yield of Soybean Crops (Glycine Max (L). Merril) This study aims to determine the type of rhizobacteria that have better ability in increasing the growth and yield of soybean crops. The research was conducted in August 2016 until December 2016, located in Angantaka Village, Abiansemal District, Badung Regency. The design used was Randomized Block Design consisting of 5 treatments, using 5 replications. This study observed plant height, number of leaves, number of branches, leaf chlorophyll content, fresh weight of plant parts above soil, fresh weight of underground plant parts, weight of oven dried above ground plant parts, weight of oven dried underground plant part, root nodules per plant, number of pods per plant, number of contained pods per plant, total weight of seed per plant, weight of 1000 seeds, soybean yield per hectare. The results showed that all four rhizobacteria RB35 (undis 1), RB36 (undis 3), RB3 (kara benguk), and RB9 (lamtoro) were able to increase the growth and yield of soybean crops. However, most effective of the four rhizobacteria are RB35 (Undis 1) and RB36 (undis 3). The use of rhizobacteria RB35 (5.59 tons ha-1) and RB36 (5.47 tons ha-1) gave the highest yield of soybean and was not significantly different between the two. Rhizobacteria RB35 (Undis 1) yielded 126.32% and rhizobacteria RB36 (Undis 3) 121.46% compared with plants without rhizobacteria or control (2.47 tons ha-1).